2008
DOI: 10.1371/journal.pgen.1000284
|View full text |Cite
|
Sign up to set email alerts
|

Chemical–Genetic Profiling of Imidazo[1,2-a]pyridines and -Pyrimidines Reveals Target Pathways Conserved between Yeast and Human Cells

Abstract: Small molecules have been shown to be potent and selective probes to understand cell physiology. Here, we show that imidazo[1,2-a]pyridines and imidazo[1,2-a]pyrimidines compose a class of compounds that target essential, conserved cellular processes. Using validated chemogenomic assays in Saccharomyces cerevisiae, we discovered that two closely related compounds, an imidazo[1,2-a]pyridine and -pyrimidine that differ by a single atom, have distinctly different mechanisms of action in vivo. 2-phenyl-3-nitroso-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…106 Our finding that different compounds from the same series have different profiles is also compelling and is consistent with previously published work demonstrating that single atom changes within a compound class can produce distinct cellular responses, which we attribute to small differences in compound structure resulting in significant fitness differences. 110 In order to derive experimental evidence for possible differences in mode of action, a parasite reduction ratio (PRR, generically “rate of killing”) 111 assay was run for six of these compounds (across both arylpyrrole and NN series) even though this assay is not a direct measure of differences in gene expression. The results (Text S1, Figure S37) suggest a common mechanism of action between the subseries and one that is distinct from artemisinin, which has previously exhibited a substantially faster killing profile.…”
Section: Resultsmentioning
confidence: 99%
“…106 Our finding that different compounds from the same series have different profiles is also compelling and is consistent with previously published work demonstrating that single atom changes within a compound class can produce distinct cellular responses, which we attribute to small differences in compound structure resulting in significant fitness differences. 110 In order to derive experimental evidence for possible differences in mode of action, a parasite reduction ratio (PRR, generically “rate of killing”) 111 assay was run for six of these compounds (across both arylpyrrole and NN series) even though this assay is not a direct measure of differences in gene expression. The results (Text S1, Figure S37) suggest a common mechanism of action between the subseries and one that is distinct from artemisinin, which has previously exhibited a substantially faster killing profile.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds with similar chemicalgenetic profiles can be grouped to reveal similar modes of action and similar targets (Parsons et al, 2006;Hillenmeyer et al, 2008). Often the gene networks that confer sensitivity or resistance to a given compound are conserved from yeast to mammalian cells Yu et al, 2008).…”
Section: Dmmbiologistsorg 640mentioning
confidence: 99%
“…Additional techniques to identify drug targets include the yeast two or three hybrid assays, temperature-sensitive mutants, GFPchimeras, protein chips and microarray analysis. Using chemogenomic assays in yeast, Yu et al [68] showed for structurally related imidalo-pyridines and -pyrimidines a differential involvement of mitochondrial dysfunction and DNA damage in their toxicity and confirmed these results in cultured human cells. Other examples for which the relevance of targets identified by yeast chemogenomic screens was shown in human cells are dihydromotuporamine C, a compound that inhibits metastasis, and molsidomine, a drug against angina [69,70].…”
Section: Yeast As Model System In Drug Safety Yeast As a Model Eukaryotementioning
confidence: 78%